The Influence of Sanctions and E-Tax Utilization on Compliance of MSMEs Taxpayers in Karawang District - Masyhuri, Masyhuri; Devi Astriani; Septiana Rahayu (Pusat Riset dan Inovasi Nasional, 2024)
Compliance level Must Tax MSMEs in Regency Karawang still low And continue to experience decline every the year. Study This aim For study The influence of tax sanctions and the use of the e-tax system on MSME taxpayer compliance. The approach used was quantitative with an explanatory research design. A sample of 100 respondents was selected using random sampling techniques from the population. MSMEs Which own Taxpayer Identification Number (NPWP) active. Analysis data done with Structural Equation Modeling (SEM) approach using SmartPLS software. The research results show that sanctions tax And utilization e-tax influential positive and significant to compliance must tax, with influence sanctions more dominant taxes. The discussion in this study is based on attribution theory, which states that behavior compliance influenced by factor external like The threat of sanctions and the ease of the e-tax system. This study focuses on MSMEs in Karawang Regency, which have experienced a decline in tax compliance, to analyze the impact of tax sanctions and the use of e-tax on taxpayer compliance.